Identification of Drought-Responsive Proteins of Sensitive and Tolerant Tea (Camellia sinensis L) Clones under Normal and Drought Stress Conditions - Rahimi, Mehdi; Kordrostami, Mojtaba; Mortezavi, Mojtaba; SafaeiChaeikar, Sanam (Current Proteomics, 2020)
Background: Tea is one of the most popular calming drinks. Drought is a major environmental factor that limited the growth and development of plants. Objective: Therefore, the identification of proteins under the drought stress conditions in tea can have an essential role in the breeding programs and tea production. Methods: For this purpose, 14 tea clones were studied under normal and drought stress conditions in two separate experiments, and the leaves of the clones were stored at −80°C. After the identification of two clones (100 and 278) as tolerant and sensitive clones, respectively, the proteomics approach was used to compare the leaf protein profile changes under both conditions. Results: The results of proteomics showed about 500 detectable protein spots, of which 250 spots were repeatable. Among the 250 reproducible spots, 16 spots responded to the drought stress, which showed the highest amount of variation among the treatments. Thioredoxin, peroxidase, superoxide dismutase, ribosomal protein, and hsp70 were mentioned among the identified proteins. These proteins were involved in various cellular functions. Conclusion: Identified proteins also had a crucial role in regulating carbohydrate and nitrogen metabolism and the scavenging of the Reactive Oxygen Species (ROS). Upregulation of proteins involved in protein processing (ribosomal protein), oxygen species scavenging, and defense (Superoxide dismutase, Peroxidase, and thioredoxin) may increase plant adaptation to drought stress. This study was the first report that showed ribosomal protein L32 was significantly changed in tea against drought stress response. Therefore, these proteins can protect the plant against drought stress. This study partially identified the drought stress proteins in the tea plant.
Keywords: protein